Non Market Approaches: Submission concerning the work programme under the framework for non-market approaches referred to in Article 6, paragraph 8, of the Paris Agreement - Villarino, Maria Eliza J.; Leonard, Stephen; Verchot, Louis V. (CGIAR System Organization, 2024)
CGIAR is pleased to share its inputs to the fifth meeting of the Glasgow Committee on Non-market Approaches (A.6.8), pursuant to the call for submissions agreed by Parties at COP28, and referred to in paragraph 14 of Decision 14C/CMA5 concerning:Themes for spin-off groups; and Existing non-market approaches under the initial focus areas of the work programme activities